Addressing transdisciplinary and participation issues to cope with rapid changes shifting marine social ecological systems. (July 2020) - Guillotreau, Patrice; Trouillet, Brice; Mahévas, Stéphanie; Pardo, Sophie
Abstract: This special section is derived from an international transdisciplinary Conference (OCEANEXT) held in 2016. It aimed at contributing to explore new initiatives mixing up scientific expertise and a participatory approach of stakeholders. This conference also ended the COSELMAR project (2013–2017), having brought together almost 170 researchers and resulted in 360 publications and communications. In this special issue, a panel of few communications were converted into peer-reviewed contributions focusing on the need for effective monitoring ahead of potential outbreaks to enhance the adaptive conditions for coastal communities and for more participation of stakeholders in the governance of social ecological marine systems. These few examples witness that transdisciplinary research on marine social ecological systems brings sound outputs, if researchers are willing to go out of their disciplinary comfort zone so as to collaborate with other disciplines and if they are able to change the way research is done within society. As a result, funding big integrating projects such as COSELMAR is essential in a marine realm constantly facing new challenges.